GAMBARAN PENGETAHUAN DAN SIKAP MAHASISWI ANGKATAN XI, XII DAN XIII TENTANG FIBROADENOMA MAMMAE DI AKADEMI KEBIDANAN HUSADA GEMILANG - Siti Rabiah Juliana; Dewi Erlina Asrita Sari (Jurnal Kesehatan Husada Gemilang, 2020)
Fibroadenoma Mammae (FAM) is a benign tumor that occurs in the breast, clear bordered and shaped lumps that can be moved. It usually occurs in women aged 20-25 years. FAM if allowed to grow will have a high risk of breast cancer and if not removed perfectly there will be relapse. Women who have been diagnosed with FAM are at risk of developing breast cancer than women with normal breasts. The prognosis will be better if done by THE U.S. Based on preliminary preliminary surveys conducted on 15 female students, 4 of them suffer from FAM disease. The purpose of the research is to find out the picture of knowledge and attitudes of students about FAM at the Academy of Midwifery Husada Gemilang Tembilahan in 2019. The study was descriptive with a cross sectional approach, the number of samples as many as 111 female students. Data collection using questionnaires. Data analysis techniques use univariate analysis. The study was conducted on September 05-06, 2019. The results of the study found the percentage of student knowledge levels about FAM the majority of 80 respondents (72%) had less knowledge and 118 respondents (100%) were kind. It is expected that the campus will increase the schedule of meetings that discuss material about FAM and students should be more active in finding information and materials in the library and on social media about FAM, and repeating the material that has been studied do not just open the book when going to the exam only.